Dyssocial behavior and personality in medical students: implications for Peruvian medical education - Perales, Alberto (2018)
(LP) of dissocial behavior indicators. Such findings compel to suspect the presence of dissocial personality in that population. On the purpose to add knowledge to this problem, the present paper analyses the concept of dissocial personality and discusses the results of a pilot-study that evaluated its presence in recently admitted students to San Marcos University´s School of Medicine. In the first evaluation, it was found that 33 out of 175 students resulted positive to dissocial behavior indicators (LP: 19%). From this group, 30 showed up for a second diagnostic evaluation; 5 exceeded the cut-off point to dissocial personality and 11 showed scores very close to it, raising suspiciousness of such development. Upon these results we claim the university must accept the responsibility to continue researching this area, create early preventive-therapeutic interventions and curricula innovations to reduce the risk of generating well trained professionals but morally handicapped.